2023
DOI: 10.3389/fimmu.2023.1192821
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent vaccines demonstrate immunogenicity and protect against Coxiella burnetii aerosol challenge

Abstract: Vaccines are among the most cost-effective public health measures for controlling infectious diseases. Coxiella burnetii is the etiological agent of Q fever, a disease with a wide clinical spectrum that ranges from mild symptoms, such as fever and fatigue, to more severe disease, such as pneumonia and endocarditis. The formalin-inactivated whole-cell vaccine Q-VAX® contains hundreds of antigens and confers lifelong protection in humans, but prior sensitization from infection or vaccination can result in delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…A P. vivax in vitro transcription/translation (IVTT) reaction protein microarray revealed antibody responses against major vivax core gene and is displayed according to the fold change in expression (x-axis, in log 2 ) and statistical significance (y-axis, in negative logarithm to the base 10 of the immunogenic blood stage antigens (Ags) in this study. This approach was supported by previous studies, which demonstrated the utility of the IVTT platform in high-throughput antigen discovery across several disease areas (84,85,86,87,88). Immune reactivity to individual antigens and antibody breadth in sera from these animals increased with each inoculation level and were statistically significantly different between inoculation levels I and III, when the animals achieved sterile immunity to a homologous SAL-1 challenge.…”
Section: Discussionsupporting
confidence: 65%
“…A P. vivax in vitro transcription/translation (IVTT) reaction protein microarray revealed antibody responses against major vivax core gene and is displayed according to the fold change in expression (x-axis, in log 2 ) and statistical significance (y-axis, in negative logarithm to the base 10 of the immunogenic blood stage antigens (Ags) in this study. This approach was supported by previous studies, which demonstrated the utility of the IVTT platform in high-throughput antigen discovery across several disease areas (84,85,86,87,88). Immune reactivity to individual antigens and antibody breadth in sera from these animals increased with each inoculation level and were statistically significantly different between inoculation levels I and III, when the animals achieved sterile immunity to a homologous SAL-1 challenge.…”
Section: Discussionsupporting
confidence: 65%
“… 63 Similarly, Q‐VAX is a licensed formalin‐inactivated whole‐cell vaccine against Coxiella burnetii , the causative agent of Q fever. 64 These studies proved the explitation of chimeric vaccine but for different strains of the same pathogens. The present study designed chimeric vaccine against two distinctly viral pathogens, namely SARS‐CoV‐2 and MPXV.…”
Section: Discussionmentioning
confidence: 86%
“…and O. tsutsugamuschi , however, surface exposed protein antigens are still likely candidates for these bacteria ( Luo et al., 2020 ). For example, the LPS from C. burnetii has been demonstrated to confer protection in both mice and guinea pigs ( Zhang et al., 2007 ; Jan et al., 2023 ).…”
Section: Antigen Selectionmentioning
confidence: 99%